The Risks of Global Financial Markets and the Importance of Credibility: Implications for Hungarian Fiscal Policy - Győrffy, Dóra (Competitio, 2005)
The central issue in the controversy about the adoption of the euro in Hungary is the difficulties associated with the fulfillment of the fiscal criterion and the possible growth sacrifice it requires. In this paper the author examines the question whether the strategy of delaying entry into the euro-zone implies that fiscal consolidation can be delayed as well. In approaching the problem the paper considers the origins and history of the present-day global financial markets and argues that given the high degree of systemic risks individual countries face responsible macroeconomic policies are crucial in minimizing vulnerability to crises. Consequently in order to avoid excessive interest rates and speculative inflows (or currency crisis in the worst case scenario) fiscal deficits in Hungary would have to be cut and credibility of fiscal policy reestablished even without EMU accession. The overall conclusion from this overview is that delaying entry in order to delay fiscal adjustment is likely to increase the trade off between real and nominal convergence instead of mitigating it. JEL classification: F33, F41, H62